Tailoring tobacco hairy root metabolism for the production of stilbenes. Issue 1 (December 2017) - Hidalgo, Diego; Georgiev, Milen; Marchev, Andrey; Bru-Martínez, Roque; Cusido, Rosa; Corchete, Purificación; Palazon, Javier
Abstract Tobacco hairy root (HR) cultures, which have been widely used for the heterologous production of target compounds, have an innate capacity to bioconvert exogenoust -resveratrol (t -R) intot- piceatannol (t -Pn) andt -pterostilbene (t -Pt). We established genetically engineered HR carrying the gene encoding stilbene synthase (STS) fromVitis vinifera and/or the transcription factor (TF) AtMYB12 fromArabidopsis thaliana, in order to generate a holistic response in the phenylpropanoid pathway and coordinate the up-regulation of multiple metabolic steps. Additionally, an artificial microRNA for chalcone synthase (amiRNA CHS) was utilized to arrest the normal flux through the endogenous chalcone synthase (CHS) enzyme, which would otherwise compete for precursors with the STS enzyme imported for the flux deviation. The transgenic HR were able to biosynthesize the target stilbenes, achieving a production of 40 μg L−1 oft -R, which was partially metabolized intot -Pn andt -Pt (up to 2.2 μg L−1 and 86.4 μg L−1, respectively), as well as its glucoside piceid (up to 339.7 μg L−1 ). Major metabolic perturbations were caused by the TF AtMYB12, affecting both primary and secondary metabolism, which confirms the complexity of biotechnological systems based on seed plantin vitro cultures for the heterologous production of high-value molecules.